Oxidative stress in occupational exposure to styrene vapors and dangerous chemicals in the shipbuilding industry - Pigini, Daniela; Paci, Enrico; Guglielmetti, Rachele; Tranfo, Giovanna; Spagnoli, Mariangela; Fetoni, Annarita; Tricarico, Laura; Sisto, Renata (Frontiers in Toxicology, 2023)
In shipbuilding industry, workers are exposed to various dangerous chemicals among which styrene must be listed. The International Agency for Research on Cancer classifies styrene as belonging to Group 2A, probably carcinogenic to humans. This study is aimed at evaluating the oxidative stress effects due to occupational exposure to styrene and the other chemicals.Styrene urinary metabolites Mandelic and Phenylglyoxylic acid, (MA, PGA respectively) and urinary biomarkers of oxidative stress, i.e. oxidation products of DNA and RNA and of proteins were measured in a group of 17 workers and compared to the concentrations found in a group of 17 healthy volunteers not exposed to chemicals.Results and discussion: Statistically significant differences were found for 8-oxo-7,8-dihydroguanine (8-oxoGua) and 8-oxo-7,8-dihydro-2'-deoxiguanosine (8-oxodGuo) concentrations that are higher in workers than in the control group. The workers performing painting are the most exposed to styrene and show higher concentrations of 8-oxo-7,8-dihydroguanosine (8-oxoGuo).Workers performing the tasks of wood refining and welding are less exposed to styrene but have higher concentrations of 8-oxoGua and 8-oxodGuo.The exposure scenario in shipbuilding is a complex one in which different xenobiotics are simultaneously present. The oxidative stress effect biomarkers, coming from the oxidation product of RNA and DNA, are promising, sensitive, but not specific.